2018
DOI: 10.1099/mic.0.000637
|View full text |Cite
|
Sign up to set email alerts
|

Identification of interactions among host and bacterial proteins and evaluation of their role early during Shigella flexneri infection

Abstract: Shigella species cause diarrhoea by invading and spreading through the epithelial layer of the human colon. The infection triggers innate immune responses in the host that the bacterium combats by translocating into the host cell cytosol via a type 3 secretion system bacterial effector proteins that interfere with host processes. We previously demonstrated that interaction of the Shigella type 3 secreted effector protein IcsB with the host protein Toca-1 inhibits the innate immune response microtubule-associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

5
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…To assess the ability of the type 3 secretion system to secrete proteins in the absence of eukaryotic cells, the T3SS was artificially activated by the addition of Congo red (7, 14, 27). Overnight cultures were back diluted, induced where appropriate with 1.2% arabinose, and cultured for 2 h at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…To assess the ability of the type 3 secretion system to secrete proteins in the absence of eukaryotic cells, the T3SS was artificially activated by the addition of Congo red (7, 14, 27). Overnight cultures were back diluted, induced where appropriate with 1.2% arabinose, and cultured for 2 h at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…To assess the ability of the type 3 secretion system to secrete proteins in the absence of eukaryotic cells, the T3SS was artificially activated by addition of Congo red (7,14,27). Overnight cultures were back diluted, induced where appropriate with 1.2% arabinose, and cultured for 2 hours at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…Recent results also indicated that Toca-1, besides interacting with IcsB, also interacts with several other S. flexneri effectors, namely IpaB, OspC3 and IpgD. The function of these interactions and possible role in the evasion of the LAP-like response, autophagy and other aspects of S. flexneri pathogenesis remains to be further investigated ( Miller et al., 2018 ).…”
Section: Interactions Of Bacterial Pathogens With Lapmentioning
confidence: 99%